2007
DOI: 10.1002/cjoc.200790266
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Minimum Electrophilicity Principle in Chemical Reactions?

Abstract: For 25 simple reactions, the changes of the hardness (Δη), polarizability (Δα) and electrophilicity index (Δω) and their cube-roots (Δη

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
36
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 51 publications
1
36
0
Order By: Relevance
“…This principle, which is called minimum electrophilicity principle (MEP), states that "it seems that there is a tendency in atoms to arrange themselves so that the obtained molecule reaches the minimum electrophilicity". 34 This principle is successfully checked for some systems 35 and it is shown that the analysis of reactivity based on the electrophilicity scale is invariant within DFT calculations. 36 Recently Morrel et al 37 provided an equation which relates the electrophilicity variation to the chemical potential and absolute hardness changes.…”
Section: Scheme 1 Intramolecular Mechanism Of Chapman Rearrangementmentioning
confidence: 97%
“…This principle, which is called minimum electrophilicity principle (MEP), states that "it seems that there is a tendency in atoms to arrange themselves so that the obtained molecule reaches the minimum electrophilicity". 34 This principle is successfully checked for some systems 35 and it is shown that the analysis of reactivity based on the electrophilicity scale is invariant within DFT calculations. 36 Recently Morrel et al 37 provided an equation which relates the electrophilicity variation to the chemical potential and absolute hardness changes.…”
Section: Scheme 1 Intramolecular Mechanism Of Chapman Rearrangementmentioning
confidence: 97%
“…MHP has been found to be valid in the cases of molecular vibrations [7], internal rotations [8][9][10][11][12], chemical reactions [13], isomer stability [14], atomic shell structure [15,16], Woodward-Hoffmann rules [17,18], aromaticity [19][20][21], electronic excitations [22], time dependent situations [23], stability of magic clusters [24], chaotic ionizations [25] and several other categories of chemical processes [26][27][28][29][30][31][32][33][34][35] and there are also certain cases like a class of non-totally symmetric vibrations [36][37][38][39][40][41] and some chemical reactions [42][43][44][45][46][47][48] where it fails. Although it does not follow directly from the MHP, a corollary to it is proposed [27] suggesting the minimum hardness value at the transition state.…”
mentioning
confidence: 99%
“…But, in fact, electrophilicity equalization is a prevailing idea of conceptual density functional theory (CDFT) sporadically segregated in chemical literature [10][11][12][13][14][15][16][17].…”
mentioning
confidence: 99%
“…Chaquin [12], by an analogy with classical electrostatics, suggests an interpretation of the Parr's 'electrophilicity index' as a 'global energy index' leading to the 'minimum electrophilicity principle'. It is expected to decrease during an exothermal process and as compared with the principle of maximum hardness; the 'principle of minimum electrophilicity' seems to be more often obeyed [13][14][15].…”
mentioning
confidence: 99%
See 1 more Smart Citation